(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In this article wewish to consider how speakers in various of the major, Stuart or Interregnumcountry house poems revisioning the Jonsonian paradigm established in ToPenshurst appropriate and attribute the supernatural. We seek to explorethe cunning and often complex syncretism with which they do so; at the sametime, we hope to clarify the extent to which Jonson’s successors attempt torewrite their Jonsonian pre-text.